Characterization, Disintegration, and Dissolution Analyses of Carrageenan-Based Hard-Shell Capsules Cross-Linked with Maltodextrin as a Potential Alternative Drug Delivery System - Muhammad Al Rizqi Dharma Fauzi; Pratiwi Pudjiastuti; Esti Hendradi; Riyanto Teguh Widodo; Mohd. Cairul Iqbal Mohd. Amin (International Journal of Polymer Science)
Hard-shell capsules commonly consist of gelatin which is not a universal material considering it is extracted from animal parts. Moreover, the mad cow disease triggered the scrutinization of the use of gelatin in pharmaceutical products. Hence, an alternative to conventional hard-shell capsules is needed. Carrageenan- (CRG-) based hard-shell capsules were successfully prepared by cross-linking CRG with maltodextrin (MD) and plasticizing with sorbitol (SOR). These CRG-MD/SOR hard-shell capsules were produced as an alternative to conventional hard-shell capsules in the oral drug delivery system (DDS). The physical properties of CRG-MD/SOR capsules were characterized using the degree of swelling, FTIR, and SEM analyses. The disintegration and dissolution profile release of paracetamol from CRG-MD/SOR hard-shell capsules was performed in an aqueous medium with three different pH levels. The degree of swelling of CRG-MD/SOR was 529.23±128.10%. The main peaks in the FTIR spectrum of CRG-MD/SOR were at 1248, 930, 847, and 805 cm−1 for ester sulfate groups, 3,6-anhydrogalactose, galactose-4-sulfate, and 3,6-anhydrogalactose-2-sulfate, respectively. The SEM analysis exhibited minuscule pores on the surface of CRG and CRG-MD/SOR at 5000 times of magnification. The CRG-MD/SOR capsules required 18.47±0.11 min on average to disintegrate. The CRG-MD/SOR dissolution was better in a weakly acidic medium (pH 4.5) than in a strongly acidic (pH 1.2) and neutral (pH 6.8) media. Based on the aforementioned results, CRG-MD/SOR capsules are the potential candidate to replace conventional hard-shell capsules.